Carbon dioxide capture and use in photobioreactors: The role of the carbon dioxide loads in the carbon footprint. (October 2020) - Deprá, Mariany C.; Dias, Rosangela R.; Severo, Ihana A.; de Menezes, Cristiano R.; Zepka, Leila Q.; Jacob-Lopes, Eduardo
Highlights: The carbon footprint in a photobioreactor under different CO2 loads was established. The most of the CO2 loads were converted to volatile organic compounds (98%). Life cycle assessment on 7 environmental burden categories was addressed. Carbon credits can be an alternative to environmental remediation and bioeconomy. Abstract: This research evaluated the carbon dioxide capture and use by Scenedesmus obliquus in a photobioreactor under different CO2 loads. Performance indicators, carbon and energy balances, sustainability indicators, and carbon credits on the photobioreactor were assessed. The results expressed that the CO2 loads of 384.9 kg/m 3 /d (15% CO2 ) provide the best trade-off for the process. For this condition, maximum biomass productivities of 0.36 kg/m 3 /d, carbon dioxide conversion rates of 0.44 kgCO2 /m 3 /d, and oxygen release rates of 0.33 kgO2 /m 3 /d were observed, reaching maximum CO2 removal efficiencies of 30.76%. Volatile organic compounds were the major products generated (>80%). However, only <3% was fixed in biomass. From the environmental and economic point of view, the net energy ratio was 3.44, while the potential carbon credit was of 0.04 USD per m 3 of culture. Finally, the use of adequate CO2 loads was also proven to be determinant to improve the global performance of the system.